Interfacial engineered PANI/carbon nanotube electrode for 1.8 V ultrahigh voltage aqueous supercapacitors. (16th April 2023) - Ji, Zhichao; Liu, Congcong; Xie, Wenhe; Liu, Shenghong; Zhang, Chao; Liu, Fuwei; Sun, Haibin; Lu, Yang; Pan, Xuexue; Wang, Chunlei; Wang, Zhuanpei
Abstract: Flexible three-dimensional interconnected carbon nanotubes on the carbon cloth (3D-CNTs/CC) were obtained through simple magnesium reduction reactions. According to the Nernst equation, the cell voltage based on these pure carbon electrodes without any additives could reach 1.5 V due to the higher di-hydrogen evolution over potential in neutral 3.5 M LiCl electrolytes. In order to improve the electrochemical performance of the electrodes, 3D-CNTs/CC electrodes covered with polyaniline barrier layer (3D-PANI/CNTs/CC) were prepared by in situ electropolymerization using interfacial engineering method. The assembled symmetric supercapacitors display a broadened voltage of 1.8 V, high areal capacitance of 380 mF cm −2, outstanding areal energy density of 85.5 μ Wh cm −2 and 84% of its initial capacitance after 20 000 charge-discharge cycles. This work demonstrated that the interface engineering strategy provides a promising way to improve the energy density of carbon-based aqueous supercapacitors by widening the voltage and boosting the capacitance simultaneously.